In Situ Investigation of the Remineralizing Effect of Saliva and Fluoride on Enamel Following Prophylaxis Using Sodium Bicarbonate - Grazziotin, Gladis Benjamina; Rios, Daniela; Honório, Heitor Marques; Silva, Salete Moura Bonifácio; Lima, José Eduardo Oliveira (European Journal of Dentistry, 2011)
Objectives: This in situ study evaluated the effect of saliva, associated or not with fluoride, on enamel previously submitted to prophylaxis using sodium bicarbonate. Methods: The study was conducted on enamel blocks submitted to in vitro prophylaxis using sodium bicarbonate. The blocks were randomly divided into 2 groups (G1/G2) and mounted on intraoral appliances wore by 10 volunteers. G1 blocks were directly exposed to saliva in situ, while blocks in G2 were exposed to saliva with fluoride (rinsing with 0.2% NaF solution during the initial minute). Enamel alterations were evaluated using surface microhardness and profilometry. Enamel hardness data were analyzed by ANOVA and Tukey tests and surface wear was evaluated using paired t test (P<.05). Results: No significant differences were found between G1 and G2 for enamel hardness and wear. The wear after prophylaxis was not different from the wear after the in situ stage. Baseline mean values of enamel hardness, after prophylaxis and after the in situ stage were 340±16.6, 329±35.7 and 354±37.8 for G1 and 338±15.6, 312±46.3 and 340±21.8 for G2, respectively. Conclusions: It was concluded that saliva alone exhibited a similar effect to saliva associated with fluoride; after 4h of in situ remineralization, there was no recovery in height of the enamel structure that had been lost due to the application of sodium bicarbonate. (Eur J Dent 2011;5:40-46)
Keywords: Saliva; Fluoride; Wear; Dental enamel